2021
DOI: 10.21873/anticanres.15066
|View full text |Cite
|
Sign up to set email alerts
|

The SOX2 Status of Disseminated Tumor Cells in Breast Cancer Patients Treated With Neoadjuvant Chemotherapy

Abstract: Background/Aim: Detection of disseminated tumor cells (DTCs) after systemic treatment predicts poor prognosis in breast cancer patients. The aim of our study was to assess the expression of stem-cell marker SOX2 on DTCs and in the primary tumor of patients treated with neoadjuvant chemotherapy (NAT). Materials and Methods: In 170 DTCpositive patients after NAT an additional slide of bone marrow aspirate was stained by double immunofluorescence to detect SOX2-positive DTCs. The SOX2 status of the primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In breast cancer (BC), SOX2 contributes to tumour malignancy and causes cells to display stromal-like features [ 41 ]. Recent studies have reported that SOX2 induces resistance to radiotherapy in BC, which plays a pivotal role in the emergence of chemotherapy resistance in tumor cells [ 17 , 42 ]. In this study, it is noteworthy that SOX2 expression was affected in cells treated with PSMD7 knockdown and overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer (BC), SOX2 contributes to tumour malignancy and causes cells to display stromal-like features [ 41 ]. Recent studies have reported that SOX2 induces resistance to radiotherapy in BC, which plays a pivotal role in the emergence of chemotherapy resistance in tumor cells [ 17 , 42 ]. In this study, it is noteworthy that SOX2 expression was affected in cells treated with PSMD7 knockdown and overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found a discordance between the HER2 status of the PT and DTCs in 29–49% of cases [ 20 , 25 , 26 , 27 ]. These results are in line with the 44% discordance found in the present study when solely differentiating between “HER2-positive” and “HER2-negative”.…”
Section: Discussionmentioning
confidence: 99%